The Palestinian context of the emergence of the Movement of Boycott, Divestment and Sanctions (BDS) movement - Idrees, Ihsan BF; Dr.Muhammad Saud (Journal of Peace, Development and Communication, 2020)
This study discusses the Palestinian context for the emergence of the " Movement of Boycott, Divestment and Sanctions " (BDS), as there are assumptions that the movement is of European and American origin, which coincides with political and theoretical trends that give the northern countries a priority in bringing about change locally. The study argues that, even if the North has a role, the movement cannot be understood without focusing on its Palestinian origin, then it deals with the interactions of the second Palestinian Intifada in and outside Palestinian society, and its impact on the crystallization of the boycott movement, as well as discusses the nature of the Palestinian parties that pushed towards the formation of the movement: Who is it, and why were these parties the most impulsive of the boycott movement, and what effect does this have on the boycott? It ends with a question about the connection of the Palestinian context to the regional and global contexts of the movement.